Analisis Variasi Bahasa dalam Film Surga yang Tak Dirindukan 2 - Slama Slama; Rifatus Surur; Irfani Husnawiyah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The diverse social backgrounds of characters in films often influence language use in communication, thereby reflecting the social conditions of the community. This study aims to describe the forms of language variation, forms of social stratification, and the relationship between language variation and social stratification in the dialogue of the film Surga yang Tak Dirindukan 2. A qualitative method with a descriptive-narrative approach was employed. Data collection involved a